EMERGENCE AND EVOLUTION OF THE ECONOMIC AND MONETARY UNION: OVERLOOK AT THE DECISION-MAKING PROCESS AND THE LEGAL INSTRUMENTS USED (FROM THE MAASTRICHT TREATY TO THE PRESENT DAY) - Dragoș–Adrian BANTAȘ; Diana Elena CĂPRIȚĂ (Challenges of the Knowledge Society, 2021)
While in the previous study we presented the premises of the emergence of what is the economic and monetary Union today, and we demonstrated that in this process the European Council had a fundamental role to play even before it was enshrined in primary Community law, whose manifestation of will takes the form of public international law acts, in the present study we will address the economic and monetary Union after its consecration in the Maastricht Treaty. Normally, this approach should lead us to analyze the institutional structure of EMU in accordance with the Treaties on which the European Union is founded, but, apparently paradoxically, careful analysis shows that even after the said consecration, the mixed use of instruments of international law to fill possible gaps in union law has not been completely abandoned.